(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article examines the problem of regional disparity in Uzbekistan football through an analysis of football clubs, stadiums, and sports schools across different regions of the country. The study explores inequalities in infrastructure, financial support, coaching quality, and youth development opportunities between urban and rural areas. Special attention is given to the impact of these disparities on player development and football competitiveness. The article also highlights existing reforms and proposes recommendations aimed at ensuring balanced and sustainable football development throughout Uzbekistan.